Control Interno A Los Inventarios Y Su Incidencia En Eficiencia Operativa De La Ferretería “Jm Ajila” Cantón Quevedo, Periodo 2023 - Barragán Fajardo, Génesis Matilde (2025)
Internal control in commercial companies is essential to ensure efficiency, transparency and compliance with organizational objectives. The "JM Ajila" hardware store, located in the Quevedo canton in 2023, deploys its efforts to optimize inventory management, including improving its operational performance. The objective of this research project is to evaluate the impact of internal inventory control on the operational efficiency of the "JM Ajila" Hardware Store, during the year 2023, to identify opportunities for improvement and strengthen business management. To carry out this evaluation, various research methods were used, such as the inductive, deductive, historical-logical and descriptive methods, using mixed approaches that combine qualitative as well as quantitative aspects. The research techniques included direct observation, interviews with the manager, as well as a questionnaire based on the COSO I model, aimed at evaluating internal control mechanisms in inventory management. The results highlighted the importance of implementing effective internal control, identifying opportunities for improvements in storage processes, reporting and even stock management. These practices contributed to reducing stockouts, minimizing differences in accounting records, as well as optimizing the use of warehouse space. The conclusions of the study emphasized the need to maintain, as well as to improve internal control to optimize operational performance, ensuring informed decision-making in addition to strengthening the competitive position of the hardware store in the market.